2019
DOI: 10.2174/1570159x17666190409143155
|View full text |Cite
|
Sign up to set email alerts
|

Using Cell Cultures for the Investigation of Treatments for Attention Deficit Hyperactivity Disorder: A Systematic Review

Abstract: Background: Advances in basic and molecular biology have promoted the use of cell cultures in a wide range of areas, including the evaluation of drug efficacy, safety and toxicity. Objective: This article aims to provide a general overview of the methodological parameters of cell cultures used to investigate therapeutic options for Attention Deficit Hyperactivity Disorder. Methods: A systematic search was performed in the electronic databases PubMed, Scopus, and DOAJ. In vitro experimental studies using ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In this scenario, it was suggested that a checklist grounded on pharmacognostic literature of medicinal plants should be completed by researchers and authors prior to publication to standardize the conduction and reporting of studies in this field (see Supplementary Materials, Table S3 ). It was also encouraged that another checklist published by Chierrito et al [ 70 ] be used for reporting experimental in vitro studies, including data on cell culture (e.g., identification of culture type, growth medium used, number of passages, incubation temperature (exact 0.0 °C), atmosphere conditions (exact 0.0% CO 2 ), and methods used).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, it was suggested that a checklist grounded on pharmacognostic literature of medicinal plants should be completed by researchers and authors prior to publication to standardize the conduction and reporting of studies in this field (see Supplementary Materials, Table S3 ). It was also encouraged that another checklist published by Chierrito et al [ 70 ] be used for reporting experimental in vitro studies, including data on cell culture (e.g., identification of culture type, growth medium used, number of passages, incubation temperature (exact 0.0 °C), atmosphere conditions (exact 0.0% CO 2 ), and methods used).…”
Section: Discussionmentioning
confidence: 99%
“…A standardized form was used to collect data on the studies’ general characteristics (e.g., authors, publication date, country), bioassay type, methodological aspects, and main results. The adapted tool for in vitro assays and the Systematic Review Center for Laboratory Animal Experimentation (SYRCLE) tool were used to assess the studies’ risk of bias and methodological quality in the Supplementary Materials (Tables S1 and S2) [ 70 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…For cell viability determination and for the anti-adhesive assay, human adherent gastric adenocarcinoma epithelial cells (AGS, ATCC CRL-1739) (Sigma-Aldrich, St. Louis, USA) were used, originating from the gastric adenocarcinoma of a 54-year-old Caucasian woman, cultivated at 37 °C/5% CO 2 (Chierrito et al 2019) in RPMI 1640 with l-glutamine medium, 10% FCS (v/v), and 1% penicillin/streptomycin (v/v). To investigate the influence of test extracts on the mitochondrial activity and the viability of AGS cells, MTT assay was performed according to Gottesmann et al (2020b).…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been widely used in studies related to periodontitis, especially with Pg. KB cells were cultured in EMEM (Biochrom), supplemented with 8.0 % (v/v) FBS (Superior, Biochrom), 1.0 % minimum essential medium (MEM) nonessential amino acids (100 × solution) (GE Health Care Products), and 50 µg/mL gentamicin (Sigma-Aldrich) at 5.0 % CO 2 /37.0 °C [40]. Passaging was performed twice a week to a maximum of 15 passages.…”
Section: Cell Culturementioning
confidence: 99%